Socio-Economic Profile of Sheep Rearing Community in Bandipora District of Jammu and Kashmir - Shah, Anees Ahmad; Khan, Hilal Musadiq; Dar, Parwaiz Ahmad; Mir, Masood Saleem (Indian Journal of Hill Farming, 2018)
A survey was conducted to study the socio-economic condition of sheep rearing community in Bandipora district of Kashmir. The district was divided into low-lying (Sonawari), medium altitude (Bandipora) and High altitude (Gurez) regions. Multi-stage random sampling was done in which 20% villages were selected from each region in the first stage through proportionate random sampling and 20 respondents from each selected village in second stage through simple random sampling. A total of 480 respondents (Sonawari=200, Bandipora=160, Gurez=120) from 24 villages were considered for the survey. It was observed that majority of the sheep rearers (59.79%) were illiterate with proportion of such respondents being significantly higher (p<0.05) in Gurez (68.33%) than Sonawari (54.0%) region. Majority (65.8%) of sheep rearers in the district were having medium size families (5-8 members) with an average family size of 6.60±0.129 with majority (86.7%) of the families being nuclear type. Overall district figure indicates that agriculture as primary and sheep farming as sub-occupation represents the source of livelihood of majority of sheep rearers in Sonawari region (67% vs 62%) and the district as a whole (36.9% vs 39.17%). Majority (49.38%) of sheep rearers in the district were falling in the income group of 11,000-20,000 Rs/month with proportion of such respondents being significantly higher (p<0.05) in Sonawari (57.5%) and Bandipora (51.88%) than Gurez (32.5%) region. The average land holding per household of sheep rearers in terms of irrigated, non-irrigated (rainfed) and total land was 5.92±0.395, 5.30±0.311 and 11.21±0.572 kanals, respectively. The average land holding/household (irrigated) was significantly higher (p<0.05) in Sonawari (10.28±0.734kanals) than Bandipora (4.56±0.504) and Gurez region (0.44±0.124). There was comparatively higher proportion (30.63%) of sheep rearers with a sheep rearing experience of 10-15 years followed by those with an experience of above 20 years (24.17%). Majority (66.88%) of the sheep rearing households involved participation of atleast one woman in various sheep farming activities. It is concluded that sheep rearing is an important secondary occupation in the district involving significant women participation but is primarily in the hands of poor and illiterate people with low income and marginal land holding.